COMPRESSION OF ECAPED TITANIUM MICRO-PILLARS FOR TWO PRINCIPAL ORIENTATIONS - David Vokoun; Jan Maňák; Karel Tesař; Stanislav Habr (Acta Polytechnica CTU Proceedings, 2020)
The thermomechanical processing by equal-channel angular pressing (ECAP) is used for certain metals and alloys in order to make their structure fine and to increase material strength. In the previous study done at our institute, grade 2 titanium was successfully processed using four consecutive route A passes via a 90 ° ECAP die with high backpressure at room temperature. Orientation dependence of compressive and tensile loading of ECAPed titanium samples was demonstrated at macro-scale. However, scarce attention has been paid so far to the mechanical behavior of ECAPed titanium samples at micro-scale. In the present study, compression experiments on titanium micropillars, fabricated using focused ion beam, are carried out for two main directions in respect to preceding ECAP pressing (insert and extrusion directions). The purpose of this study is to discuss the orientation dependence of mechanical response during compression of the as-ECAPed titanium micro-pillars.